Referral of touch and ownership between the hands and the role of the somatosensory cortices. - Michael Schaefer (Public Library of Science (PLoS), 2013)
Recent studies have shown that the feeling of body ownership can be fooled by simple visuo-tactile manipulations. Perceptual illusions have been reported in which participants sense phantom touch seen on a rubber hand (rubber hand illusion). While previous studies used homologous limbs for those experiments, we here examined an illusion where people feel phantom touch on a left rubber hand when they see it brushed simultaneously with brushes applied to their right hand. Thus, we investigated a referral of touch from the right to the left hand (across the body midline). Since it is known from animal studies that tactile illusions may alter early sensory processing, we expected a modulation of the primary somatosensory cortex (SI) corresponding to this illusion. Neuromagnetic source imaging of the functional topographic organization in SI showed a shift in left SI, associated with the strength of the referral of touch. Hence, we argue that SI seems to be closely associated with this perceptual illusion. The results suggest that the transfer of tactile information across the body midline could be mediated by neurons with bilateral tactile receptive fields (most likely BA2).